Children's Perception of Choice in Their Play at Home, in the School Playground and in the Out-of-School Club - Peter King (2013)
In the United Kingdom and Republic of Ireland, with the exception of England, each county has their own Government play policy or strategy. Each document identifies the importance of children’s play in all areas of their lives. These policies and strategies are based on a definition of play being freely-chosen by the child. This is an adult generated definition of play, based on rhetoric with little research from a child’s perspective as to whether being freely chosen is a defining characteristic. The social construction of childhood stresses the importance of children as co-constructors of their lives; however children’s voices and views are not always represented accurately in policy development and policy implementation. There is already conflict in policy development and subsequent implementation of policy by practitioners in other areas of children’s lives, for example in early years education. This conflict may emerge in implementing play policies and strategies based on adult generated definitions around choice rather than a child’s perception of whether and in what ways, choice is important. This thesis investigated children’s levels of perceived choice in their free play when playing at home, in the school playground and the out of school club. The aims of the research were: What do children choose to play at home, in the school playground and the out of school club? How much choice do children perceive in these self-defined play activities? Does children’s perception of choice differ across context? Does children’s perception of choice differ in relation to social context? This thesis adopted a critical realism approach within an ecosystemic theoretical framework using a mixed-method sequential two study process. Study 1 was quantitative and involved the development a self-administered questionnaire, the Play Detective Diary. The Play Detective Diary allowed children to record who they played with and who made decisions in the play. Study 2 was both quantitative and qualitative where an experimental procedure was developed, the Manipulation of Affordance Scenario Task (MAST). This pictorial based task manipulated the structural, functional and social affordances of children’s play and children’s responses about choice were recorded through interviews. The results from both studies found that children’s perception of choice varied across context (home, school playground and out of school club) and the variation in choice was strongly influenced by who children were playing with. When the structural, social and functional affordances were manipulated there was a reduction in choice as a result of; other people controlling the play (being told what to do and takes over play); the play activity being inhibited (play being distracted and lack of resources) and; the play space being limiting (play space too small and play space specific to the play activity). When playing with other children or with adults there was an increase in the perceived level of choice in relation to social affordances only. Children described this as being due to their play being enhanced (more variety and provides support) or the child feeling as though they were able to dominate the play (tell others what to do). The reasons children gave for changes in their perceived level of choice most often related to functional-social affordance reasons; this is a combination of the activity and the people involved in the activity.The investigation of choice in children’s play showed children perceived a variation in perceived choice in relation to context and who is involved in their play. Children do not need to have all the choice on what, how, who, when and where they play. Children have to exercise and negotiate choice in their play, and this aspect is important with respect to play policy and strategy development, and subsequent implementation through professional practice. The social construction of childhood revolves around participation, decision making and children being active agents in the process. By providing children a voice and allowing their perceptions to be explored, this can aid in policy development, and in turn support professional practice and reduce potential conflict between policy development and implementation. This is discussed in relation to children’s rights, play theory and play policy and practice across children’s services. A choice continuum is proposed to support children’s play across different professional contexts.